Cultivation and Regression Analysis of Children’s Mental Toughness under the Intervention of Sports Perseverance Mechanism - Fei Yang; Yanan Wang; Luobin Zhang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
With the rise of exercise psychology, society emphasizes the physical and psychological health of children and adolescents. If sports intervention is performed regularly, children and adolescents will develop a more resilient mindset, greater self-assurance, and a greater tolerance for setbacks. However, the relevant research lacks quantitative analysis and fails to investigate the mediation effect of the mechanism underlying sports perseverance. Consequently, this research investigates the cultivation and regression analysis of children's mental toughness under the sports perseverance mechanism. First, a model was developed to examine the sports perseverance intervention aimed at improving the mental toughness of youngsters. Next, a multi-factor cointegration test was conducted on the time series of the measured values of children's mental toughness in response to sports perseverance. In addition, the error correction model and the breakpoint regression model were developed to identify the instances in which the time series diverge from the equilibrium state and return to normal. Experiments were conducted to get the test results of the presented models, which demonstrate their efficacy.